PENGARUH BELANJA PEMERINTAH BIDANG PENDIDIKAN, KESEHATAN DAN PERLINDUNGAN SOSIAL TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Angga Setiawan; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the impact of government spending on education, health, and social protection on the Human Development Index in Indonesia. The method used in this study is a panel data regression analysis method consisting of 34 provinces in Indonesia during the 2015-2018 period. Variables in this study include the Human Development Index (HDI) sourced from the central statistical agency or Badan Pusat Staistik (BPS), government spending in education, health and social protection are source from the General Directorate of Financial Balance or Direktorat Jendral Perimbanganan Keuangan (DJPK). The results showed that government spending in education and government spending in health had a positive and significant effect on the Human Development Index (HDI) value, while government spending on social protection had a negative and significant effect on the human development index (HDI) value. Keywords: Human Development Index, Education Spending, Health Spending, Social Protection Spending.